Donor's graft ex vivo T‐cell depletion with fludarabine reduces graft‐versus‐host disease signs and improves survival after intestinal transplantation – an experimental study. (16th July 2020) - Vela, Maria; Stringa, Pablo; González‐Navarro, Pablo; Machuca, Mariana; Pascual‐Miguel, Bárbara; Mestre, Carmen; Arreola, Nidia M.; Papa‐Gobbi, Rodrigo; Navarro‐Zapata, Alfonso; Pires‐Lobo, Sara C.; Andrés, Ane M.; Hernández‐Oliveros, Francisco; et al.
Summary: Intestinal passenger T leukocytes are responsible for graft‐versus‐host disease (GvHD) in intestinal transplantation (ITx). We hypothesized that ex vivo fludarabine treatment of the bowel graft would diminish the risk of GvHD and improve overall survival post‐transplant. We performed isolated heterotopic small bowel transplantations from Lewis (LEW) to Brown Norway (BN) rat strains, which generated GvHD signs from the fourth day post‐transplant. These symptoms included rash, weight loss, piloerection, and diarrhea. The grafts of one of the experimental groups were immersed and sealed in cold Celsior preservation solution with 1000 µm fludarabine for 1 h, prior to its implantation into recipient animals. No histological signs of intestinal tissue alterations were observed after fludarabine treatment. Fludarabine‐treated bowel recipients showed significantly later and milder clinical signs of GvHD and reduced total donor cell chimerism, as determined by flow cytometry using strain‐specific anti‐HLA antibodies. Additionally, fludarabine treatment prolonged recipients' overall survival (13.5 days ± 0.3 days vs. 9.2 days ± 0.5). We conclude that active modification of the intestinal leukocyte composition is advantageous in our ITx animal model. Immunosuppression with fludarabine during the surgical procedure, which could be translated directly to the clinic, protects bowel recipients from GvHD and improves overall post‐transplant survival.